Balinese mask 3D modeling design using procedural nodes for digital preservation attempt - Kadek Satria; Pratama, Tito Ari; Rosita, Ely (Universitas Indraprasta PGRI, 2025)
Digital preservation of Indonesian art and culture has become an increasingly essential practice in the era of the Internet of Things, where accessibility and longevity of cultural heritage are paramount. This research focuses on the digital preservation process through a case study of Balinese art and culture, with a particular emphasis on the iconic Balinese masks. The study involved high-resolution photography of Balinese masks housed at the Setia Darma House of Mask and Puppets, which served as the foundation for creating detailed 3D models. This digital asset will be broken down in several steps of 3D modeling using Blender software and specifically utilized the procedural nodes to achieve lower file size but maintain the image quality. The result will show the significant effort to preserve art and culture in digital media by utilizing 3D software technology to create better visuals with effective file sizes.